An accountability evaluation for the International Food & Beverage Alliance's Global Policy on Marketing Communications to Children to reduce obesity: A narrative review to inform policy. (29th April 2019) - Kraak, Vivica I.; Rincón‐Gallardo Patiño, Sofia; Sacks, Gary
Summary: United Nations (UN) organizations have urged governments to restrict the marketing of unhealthy food and nonalcoholic beverage products to children. This study conducted an accountability evaluation for the International Food & Beverage Alliance's (IFBA's) Global Policy on Marketing Communications to Children (Global Policy) compared with UN and other best‐practice recommendations. We used the National Academy of Medicine's LEAD (ie, locate, evaluate, assemble evidence to inform decisions) framework to identify evidence (January 2004 to October 2018). We assigned a progress score (ie, none, limited, some, extensive) for five accountability steps. No progress was made to appoint an empowered body to evaluate IFBA's Global Policy. IFBA and the Access to Nutrition Foundation made some progress to take and share the account. Diverse actors made no progress to hold IFBA to account for nonadherence or to strengthen accountability structures for future compliance. IFBA could strengthen its Global Policy to align with best practices. UN organizations and other stakeholders should encourage IFBA firms to restrict the marketing of unhealthy foods and beverages to reduce children's obesity risk. This evaluation is relevant to all firms and industry associations that market products to children that undermine their diet and health.